The ecomorphology of Caribou (Rangifer tarandus): a geometric morphometric study. [version 2; peer review: 2 approved, 1 approved with reservations] - Ariane Burke; Ana Belén GALÁN LÓPEZ; Sandrine Costamagno (Open Research Europe)
Paleolithic reindeer (Rangifer tarandus) was a key species for human populations in western and central Europe during much of the Paleolithic period. In Southwestern France, and in particular during the Magdalenian, reindeer frequently figures among the privileged prey of hunter-gatherer groups. However, and despite numerous attempts to reconstruct the migratory behaviour of Paleolithic reindeer, there is no agreement on the degree of mobility of this prey. Modern ethological data indicate that reindeer herds adopt different mobility strategies depending on the type of habitat and the topography of the environment. Through metapodial bones and phalanges cross-sections, our project ‘Reconstructing habitat type and mobility patterns of Rangifer tarandus during the Late Pleistocene in Southwestern France: an ecomorphological study’ (Emorph) quantifies the link between habitat type, mobility, bone density and morphology using computer tomography (CT) and geometric morphometry (GMM). Based initially on the study of extant caribou populations with distinct migratory behaviours, the results obtained could be applied to several Magdalenian assemblages from southwestern France in the future, with the aim of reconstructing the mobility of these tardiglacial reindeer.